Evaluación de las condiciones la alfabetización los estudiantes con discapacidad intelectual en contexto inclusivo - de Oliveira, Anna Augusta Sampaio [UNESP] (Mary Lou Fulton Teacher College, 2015)
The issue of evaluation in the area of intellectual disabilities, an inclusive perspective, is still relatively unexplored in research and educational practice. This study presents results of research on the performance in early literacy. We evaluated 32 students with intellectual disabilities, the 2ndyear of elementary school, one of the central regions of São Paulo. The results show learning opportunities as well as difficulties in the area of reading and writing of these students.
Avaliação da condição de alfabetização de estudantes com deficiência intelectual no contexto inclusivo
Assessment of students with intellectual disabilities literacy condition in inclusive context
Keywords: Alphabetization; Assessment; Intellectual disabilities